Hambatan Epistimologis Siswa dalam Menyelesaikan Masalah Sistem Persamaan Linear Dua Variabel - Samsul Maarif; Rokhyani Nur Setiarini; Nurafni Nurafni (Universitas Syiah Kuala, 2020)
Many students make mistakes in solving mathematical problems, including the problem of the System of Linear Equations in Two Variables (SLETV). This research was a descriptive study using a qualitative research approach to analyze students' epistemological obstacles in solving SLETV problems. The respondents of this study were 53 Year 9 students of SMP Islam Raudlotul Hikmah who had learned SLETV. The instrument used was a mathematical problem-solving ability test and interview guideline. The data analysis was conducted by analyzing the answers of 53 respondents to three types of epistemological obstacles. Five respondents were also interviewed to find out more about the obstacles that occurred. The results showed three types of students' epistemological obstacles in solving SLETV problems: conceptual obstacle, procedural obstacle, and operational, technical obstacle. The findings of epistemological obstacles in this study showed the same pattern as previous research findings, although the material was different. Thus, it can be used as a basis for teachers to improve learning strategies related to SLETV and other mathematical materials.